The molecular biology and biotechnology of flowering - Jordan, Brian R. (CABI Publishing, 2006)
Provides an overview of the molecular mechanisms associated with flowering. This book explores three main themes: the external and internal regulation of flowering, floral development, and fertilisation and gametophyte development, and also includes chapters on the evolution of flowers, floral senescence and apomixis.